2010
DOI: 10.1007/s00262-010-0929-7
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls of vaccinations with WT1-, Proteinase3- and MUC1-derived peptides in combination with MontanideISA51 and CpG7909

Abstract: T cells with specificity for antigens derived from Wilms Tumor gene (WT1), Proteinase3 (Pr3), and mucin1 (MUC1) have been demonstrated to lyse acute myeloid leukemia (AML) blasts and multiple-myeloma (MM) cells, and strategies to enhance or induce such tumor-specific T cells by vaccination are currently being explored in multiple clinical trials. To test safety and immunogenicity of a vaccine composed of WT1-, Pr3-, and MUC1-derived Class I-restricted peptides and the pan HLA-DR T helper cell epitope (PADRE) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…88 Although patient numbers were very limited in these studies, their results imply that immunologic responses might be inversely correlated with Treg frequencies. 81,87 Therefore, Treg depletion before vaccination might help augment antileukemic responses. Berneman et al demonstrated that WT1-targeted DC vaccination can prevent relapse by augmenting CD8 ϩ immune response without an increase in Tregs.…”
Section: Treg Depletion Before Vaccination To Augment Anti-aml Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…88 Although patient numbers were very limited in these studies, their results imply that immunologic responses might be inversely correlated with Treg frequencies. 81,87 Therefore, Treg depletion before vaccination might help augment antileukemic responses. Berneman et al demonstrated that WT1-targeted DC vaccination can prevent relapse by augmenting CD8 ϩ immune response without an increase in Tregs.…”
Section: Treg Depletion Before Vaccination To Augment Anti-aml Responsesmentioning
confidence: 99%
“…In vivo, a few vaccination studies monitored Treg frequencies before and after vaccination. 80,81,87,88 Vaccination with allogeneic or autologous AML cells transduced with a lentivirus expressing CD80 and IL-2 (ie, LV-CD80/IL-2) increased Treg frequencies. 88 Although patient numbers were very limited in these studies, their results imply that immunologic responses might be inversely correlated with Treg frequencies.…”
mentioning
confidence: 99%
“…Many studies have investigated the use of these target antigens as possible vaccine strategies in other hematologic malignancies [119,120]. However, a recent study showed that these vaccine strategies employed on advanced stage cancer patients could not produce T cells that proliferated nor secreted cytokines upon peptide stimulation and in fact T cells were depleted rather than rescued after vaccination [118].…”
Section: Myeloma Vaccinesmentioning
confidence: 99%
“…Another candidate tumor antigen is the mucin 1 protein (MUC1) [118]. Many studies have investigated the use of these target antigens as possible vaccine strategies in other hematologic malignancies [119,120].…”
Section: Myeloma Vaccinesmentioning
confidence: 99%
“…However, administration of a vaccine without a suitable adjuvant is unlikely to elicit an effective immune response and may lead to tolerance. 21,22 The glycolipid a-galactosylceramide (a-GalCer) has recently been shown to be a useful adjuvant for whole tumor cell vaccination by eliciting stimulatory interactions between dendritic cells (DCs) and natural killer T (NKT) cells. [23][24][25][26] When DCs acquire cellular material from irradiated tumor cells that have been treated with a-GalCer, the protein content is presented as peptides via major histocompatibility complex (MHC) molecules to CD4 1 and CD8 1 T cells, whereas the a-GalCer is presented via the MHClike molecule CD1d to NKT cells.…”
Section: Introductionmentioning
confidence: 99%